2019
DOI: 10.1038/s41401-019-0267-z
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of aryl sulfonamide-selective Nav1.7 inhibitors with a highly hydrophobic ethanoanthracene core

Abstract: Nav1.7 channels are mainly distributed in the peripheral nervous system. Blockade of Nav1.7 channels with small-molecule inhibitors in humans might provide pain relief without affecting the central nervous system. Based on the facts that many reported Nav1.7-selective inhibitors contain aryl sulfonamide fragments, as well as a tricyclic antidepressant, maprotiline, has been found to inhibit Nav1.7 channels, we designed and synthesized a series of compounds with ethanoanthracene and aryl sulfonamide moieties. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It selectively inhibits the Na V 1.7 channel but not the Na V 1.4 and 1.5 channel. Many other references reported the selective inhibition of the Na V 1.7 channel. To achieve that in our optimization process, we can combine classifiers of Na V 1.5 or Na V 1.4 in future work. Another advantage is that building such a simple classifier does not require a lot of data.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It selectively inhibits the Na V 1.7 channel but not the Na V 1.4 and 1.5 channel. Many other references reported the selective inhibition of the Na V 1.7 channel. To achieve that in our optimization process, we can combine classifiers of Na V 1.5 or Na V 1.4 in future work. Another advantage is that building such a simple classifier does not require a lot of data.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Besides, the effects of GAS on TTX-sensitive sodium current were recorded on DRG neurons. While Na V 1.6 was mainly distributed in medium and large diameter neurons ( Chen et al, 2020 ), the small-diameter neurons that were concerned in this study expressed Na V 1.7 (TTX-sensitive), Na V 1.8 and Na V 1.9 (TTX-resistant) ( Wang et al, 2020 ). In this section, since the current of Na V 1.7 couldn’t be directly observed, the TTX-sensitive sodium current obtained by subtracting the current after TTX processing from the total Na current, indicating the large component of the TTX-sensitive sodium current was Na V 1.7.…”
Section: Resultsmentioning
confidence: 78%
“…Multiple studies have suggested that a group of molecules called arylsulfonamides could play a significant role in finding a specific inhibitor of the Na V 1.7 isoform [ 63 , 64 ]. Moreover, certain sodium channel blockers such as lidocaine have been shown to enhance the inhibitory effect arylsulfonamides have on Na V 1.7 channels.…”
Section: Pharmacological Management In Diabetic Peripheral Neuropathymentioning
confidence: 99%
“…This discovery lead researchers to believe that a selective inhibition of this channel might prove beneficial in pain treatment in various pathological states [61,62]. Multiple studies have suggested that a group of molecules called arylsulfonamides could play a significant role in finding a specific inhibitor of the Na V 1.7 isoform [63,64]. Moreover, certain sodium channel blockers such as lidocaine have been shown to enhance the inhibitory effect arylsulfonamides have on Na V 1.7 channels.…”
Section: Sodium Channel Blockersmentioning
confidence: 99%